A Scientific Approach to Ethics Developing Greater Respect for Ethics in Business and Society - Storchevoy, Maxim (Springer International Publishing, 2018)
This book suggests that normative ethics should be developed as a social science, and that this will improve its reputation in business and society. Storchevoy defines four criteria of a good scientific method (clear definitions, correct logic, empirical verification, accurate measurement) and demonstrates how normative ethics can make use of them. He provides a historical review of the methodological evolution of normative ethics and outlines how it was moving in a nonlinear way towards this scientific development by the 16th century. A Scientific Approach to Ethics challenges the reputation of ethics among many within business and business schools as unscientific and argues that it can come to be seen as a scientific discipline able to reveal universal moral truth.